2015
DOI: 10.4314/sajas.v45i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Milk fatty acid composition and conjugated linoleic acid content of Jersey and Fleckvieh x Jersey cows in a pasture-based feeding system

Abstract: A number of fatty acids (FAs), such as omega-3, omega-6 and conjugated linoleic acid (CLA), which are present in the milk from dairy cows are considered essential FAs and beneficial nutrients for humans. The aim of the study was to compare the milk FA content, particularly the CLA, omega-3 and omega-6 FA content of the milk fat of Jersey and Fleckvieh x Jersey (F x J) cows in a pasture-based feeding system. All cows were fed the same diet consisting of kikuyu-ryegrass pasture in a rotational grazing system sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
2
3
1
1
Order By: Relevance
“…Feeding lactating ewes with pasture or lipid supplements rich in PUFA results in milk rich in MUFA and PUFA (Mierlita et al, 2011). In accordance with the present results, similar seasonal effect with a decrease in SFA, and an increase in MUFA and PUFA of the milk produced by lactating ewes (Atti et al, 2006;Meluchova et al, 2008;Abilleira et al, 2009;Carloni et al, 2010), cows (Sasanti et al, 2015) or goats (Sampelayo et al, 2007), under grazing pasture feeding conditions, were observed in previous studies.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Feeding lactating ewes with pasture or lipid supplements rich in PUFA results in milk rich in MUFA and PUFA (Mierlita et al, 2011). In accordance with the present results, similar seasonal effect with a decrease in SFA, and an increase in MUFA and PUFA of the milk produced by lactating ewes (Atti et al, 2006;Meluchova et al, 2008;Abilleira et al, 2009;Carloni et al, 2010), cows (Sasanti et al, 2015) or goats (Sampelayo et al, 2007), under grazing pasture feeding conditions, were observed in previous studies.…”
Section: Resultssupporting
confidence: 92%
“…Papaloukas et al, (2016) reported that bulk ovine milk produced by various sheep breeds fed on grazing pasture in mountainous areas in Northern Greece showed cis-9, trans-11 CLA values of 0.58, 0.98 and 1.12% FAME in winter, spring and summer, respectively. Seasonal variations of C18:2 cis-9, trans-11 CLA in milk from cows (Chion et al, 2010;Sasanti et al, 2015) or goats (Milewski et al, 2018) produced under grazing pasture feeding conditions were also reported. Signorelli et al, (2008) examined the FAs composition of ovine milk produced by lactated ewes under the same combined pasture and concentrate feeding conditions and found cis-9, trans-11 CLA levels of 1.905%, 1.958% and 1.617% FAME for the Italian breeds, Altamurana, Gentile di Puglia and Sarda, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The effects of diet and breed on FA content are shown in Table 1. In contrast with an earlier study which showed that breed and lactation stage affected the content in milk fat and some FAs (Sasanti et al, 2015), the present study showed that the FA content of the milk of cows was not affected by breed (P >0.05) except for C8:0 (P <0.008) and C12:0 (P <0.026). There was no (P >0.05) lactation stage effect, although a linear trend was observed for most FAs, however, with no significant difference between means.…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, the increase in CLA and C18:3n-3, when cows were put back on pasture (Pasture 2) was higher (P <0.05) than the initial levels on pasture (Pasture 1). This higher content is probably related to lactation stage, although was not significant between means, similar to a study by Sasanti et al (2015) which showed that while CLA levels differed between breeds, higher levels were shown towards the end of the lactation period.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation